A Multi-Ingredient Nutritional Supplement in Combination With Resistance Exercise and High-Intensity Interval Training Improves Cognitive Function and Increases N-3 Index in Healthy Older Men: A Randomized Controlled Trial - Bell, Kirsten E.; Fang, Hanna; Snijders, Tim; Allison, David J.; Zulyniak, Michael A.; Chabowski, Adrian; Parise, Gianni; Phillips, Stuart M.; Heisz, Jennifer J. (Frontiers in Aging Neuroscience, 2019)
We aimed to evaluate the effect of multi-ingredient nutritional supplementation, with and without exercise training, on cognitive function in healthy older men. Forty-nine sedentary men (age: 73±6years [mean±SD]; body mass index: 28.5±3.6kg/m2) were randomized to consume a supplement (SUPP n=25; 1500mg n-3 polyunsaturated fatty acids, 30g whey protein, 2.5g creatine, 500IU vitamin D, and 400mg calcium) or control beverage (CON n=24; 22g maltodextrin) twice daily for 20wk consisting of Phase 1: SUPP/CON followed by Phase 2: 12-wk resistance exercise training plus high-intensity interval training, while continuing to consume the study beverages (SUPP/CON+EX). At baseline, 6wk, and 19wk we assessed cognitive function (Montréal Cognitive Assessment [MOCA]), memory (word recall during the Rey Auditory Verbal Learning Test [RAVLT]), and executive functions (working memory inhibition control), and nutrient bioavailability. We did not observe changes to any aspect of cognitive function after Phase 1; however, significant improvements in the following cognitive function outcomes were detected following Phase 2: MOCA scores increased (6wk: 23.5±3.3 vs. 19wk: 24.4±2.5, p=0.013); number of words recalled during the RAVLT (6wk: 6.6±3.6 vs. 19wk: 7.6±3.8, p=0.047); and reaction time improved (6wk: 567±49ms vs. 19wk: 551±51ms, p=0.002). Although between-group differences in these outcomes were not significant, we observed within-group improvements in composite cognitive function scores over the course of the entire study only in the SUPP group (Δ = 0.58±0.62, p=0.004) but not in the CON group (Δ = 0.31±0.61, p=0.06). We observed a progressive increase in n-3 index, and a concomitant decrease in the ratio of arachidonic acid (ARA) to eicosapentaenoic acid (EPA) within erythrocyte plasma membranes, in the SUPP group only. At week 19, n-3 index (r=0.49, p=0.02) and the ARA:EPA ratio (r=-0.44, p=0.03) were significantly correlated with composite cognitive function scores. Our results show that 12 weeks of RET + HIIT resulted in improved MOCA scores, word recall, and reaction time during an executive functions task; and suggest that a multi-ingredient supplement combined with this exercise training program may improve composite cognitive function scores in older men possibly via supplementation-mediated alterations to n-3 PUFA bioavailability. This trial was registered at ClinicalTrials.gov (NCT02281331).